Rosario+Vampire. Season II 11 - Ikeda, Akihisa, 1976- (Shonen Jump advanced., 2013)
"Average human teenage boy Tsukune accidentally enrolls at a boarding school for monsters--no, not jocks and popular kids, but bona fide werewolves, witches, and unnameables out of his wildest nightmares! And now he's a sophomore!"--Cover.